What health threats does climate change pose to sports?: a classic Delphi study among multi- and transdisciplinary experts in medicine and sports - Schneider, Sven; Niederberger, Marlen; Kurowski, Luke; Bade, Luisa (Science & sports, 2024)
Objectives - The World Health Organization has identified climate change as “the single biggest health threat facing humanity”. Climate change will affect athletes in particular. The literature lacks thorough, scientifically based studies on what health effects climate change will have on athletes. The aim of this study was to systematically analyze the emerging climate change-related health effects on outdoor athletes. - Equipment and methods - We conducted a classic, asynchronous Delphi study among a panel of experts. To maintain a multidisciplinary approach, 24 medical doctors from different specialties and 24 experts from the eight largest German outdoor sports associations were recruited. - Results - According to the expert panel, outdoor sports will be increasingly confronted with the following six risk factors: temperature-related risks, accident and injury risks, UV-related risks, respiratory risks, infection and intoxication risks, and mental and psychosocial risks. - Conclusion - This empirical aggregation of knowledge from scientists, sports organizations, clubs, trainers, and professional athletes may lay the foundation for future approaches that could prevent or intervene in climate change driven health risks in outdoor sports. - Résumé - Objectifs - L’Organisation mondiale de la santé a identifié le changement climatique comme « la plus grande menace sanitaire à laquelle l’humanité est confrontée ». Le changement climatique affectera tout particulièrement les athlètes. La littérature manque d’études approfondies et scientifiquement fondées sur les effets du changement climatique sur la santé des athlètes. L’objectif de cette étude était d’effectuer une « analyse systématique » des effets émergents du changement climatique sur la santé des athlètes de plein air. - Matériel et méthodes - Nous avons mené une étude Delphi classique et asynchrone auprès d’un panel d’experts. Pour maintenir une approche multidisciplinaire, 24 médecins de différentes spécialités et 24 experts des huit plus grandes associations allemandes de sports de plein air ont été recrutés. - Résultats - Selon le panel d’experts, les sports de plein air seront de plus en plus confrontés aux six facteurs de risque suivants : risques liés à la température, risques d’accidents et de blessures, risques liés aux rayons UV, risques respiratoires, risques d’infection et d’intoxication, et risques psychosociaux. - Conclusion - Cette analyse des connaissances des scientifiques, des organisations sportives, des clubs, des entraîneurs et des athlètes professionnels pourrait jeter les bases d’approches futures susceptibles de prévenir ou au moins d’intervenir sur les risques sanitaires liés au changement climatique dans les sports de plein air.